Women on the Move: Body, Memory and Femininity in Present-Day Transnational Diasporic Writing, editado por Silvia Pellicer-Ortín y Julia Tofantšuk - Duce Sarasa, Violeta (Miscelánea: A Journal of English and American Studies, 2019)
.